PROS and CONS of linear and nonlinear seismic analyses for existing URM structures: Application to a historical building. (August 2021) - Sandoli, Antonio; Pacella, Gaetana; Cordasco, Emilia Angela; Calderoni, Bruno
Abstract: Seismic capacity assessment of existing buildings is of paramount importance for mitigating the seismic risk in earthquake-prone areas. In Europe, the next version of Eurocode 8 and the current version of the Italian standards suggest the adoption of both linear and nonlinear approaches to perform seismic analyses of existing masonry buildings. This paper discusses with the main issues concerning linear and nonlinear analyses methodologies provided by the Italian standards for existing unreinforced masonry buildings. An historical building located in Southern Italy, representative of the Mediterranean basin buildings, has been chosen as a case study and modelled through the equivalent frame model. According to the Italian standards, the influence of in-plane stiffness of floors and spandrels on the overall seismic capacity of the structure has been considered in the analyses. Beyond the code prescriptions, the effect of different ultimate drifts values assumed for the spandrels on nonlinear behavior of the structure has been analysed. The results of two types of linear analyses (lateral static force method and modal response spectrum analysis) have been compared among them and with those provided by the nonlinear static method. Conclusions show that either behavior and overstrength factors provided by the Italian standards are conservative than those estimated through the nonlinear static analyses. Moreover, it has been remarked that the value of ultimate drift adopted for the spandrel can affect significantly the nonlinear response of the structures, although this topic still represents an open issue.